2016
DOI: 10.3168/jds.2015-9843
|View full text |Cite
|
Sign up to set email alerts
|

Toward improved postpartum cyclicity of primiparous dairy cows: Effects of genetic merit for production traits under contrasting feeding systems

Abstract: 1 to 14 of lactation (+3.8 kg/wk) than cows in the low feeding system. No effect of feeding system or milk yield was observed on C-LA. Prolonged luteal phases were frequent (18% of cows) and were not associated with either breed or genetic group. Ovarian cycles were longer for Holstein than for Normande cows (+1.7 d) because of a longer luteal phase and a longer interluteal interval. Results of the study could be useful to establish strategies to manage declining reproductive performances at genetic and enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…The metabolites recorded in the present study suggest that cows were in an acceptable energy balance as the mean values are within the threshold of healthy cows as mentioned previously. Findings similar to those of O' Sullivan et al (2019b) and other studies (Walsh et al, 2008;Bedere et al, 2016) were found in the present study, where progesterone variables used to identify PPAI were not affected by genotype. The poor fertility subindex in this study is just below the current national average (26.5 vs. 37.6, ICBF) and did not have a negative effect on the uterine recovery parameters recorded.…”
Section: Genetic Effectsupporting
confidence: 92%
“…The metabolites recorded in the present study suggest that cows were in an acceptable energy balance as the mean values are within the threshold of healthy cows as mentioned previously. Findings similar to those of O' Sullivan et al (2019b) and other studies (Walsh et al, 2008;Bedere et al, 2016) were found in the present study, where progesterone variables used to identify PPAI were not affected by genotype. The poor fertility subindex in this study is just below the current national average (26.5 vs. 37.6, ICBF) and did not have a negative effect on the uterine recovery parameters recorded.…”
Section: Genetic Effectsupporting
confidence: 92%
“…Indeed, Nebel and McGilliard (1993) and Bello et al (2013) found that herds with high genetic merit for milk yield had poor fertility status, which was not observed between cows within herds. Our results show that, in both breeds, cows in the milk group have delayed cyclicity compared with the content group (Bedere et al, 2016a). Further studies are needed to confirm whether cows in the content group have impaired fertility because selecting for fat content may have impaired embryo survival or not.…”
mentioning
confidence: 71%
“…It can be hypothesized that dairy cows with high genetic merit for fat and protein content preserve their reproductive performance while producing the same amount of milk solids than cows with high genetic merit for milk yield. A previous study showed that primiparous dairy cows with high genetic merit for fat and protein content had an earlier commencement of luteal activity than those with high genetic merit for milk yield in 2 contrasted breeds (dairy vs. dual-purpose cows) and 2 contrasted feeding systems (high vs. low inputs; Bedere et al, 2016a). This was a promising result to establish strategies to cope with reproductive decline and maintain productive performance.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Pelvic floor dysfunction (PFD), a type of common gynecological disease in women, refers to the pelvic tissues that are affected by various pathogenesis and the external environment. This affects decreased immune ability and weakened structure, which leads to the susceptibility of pelvic organ displacement due to injured tissues, which leads to the abnormal location of organs and induces functional PFD ( 1 3 ). Clinical data ( 4 ) indicate that physical rehabilitation therapy, combined with herbal treatment, can effectively enhance pelvic functions and increase perineal muscle strength.…”
Section: Introductionmentioning
confidence: 99%